PsycEXTRA Dataset 2009
DOI: 10.1037/e729142011-001
|View full text |Cite
|
Sign up to set email alerts
|

2007 National Roadside Survey of Alcohol and Drug Use by Drivers: Alcohol Results

Abstract: Amy Berning served as the project's Contracting Officer's Technical Representative. The National Institute on Alcohol Abuse and Alcoholism (NIAAA) provided funding and support for the assessment of alcohol use disorders. The National Institute on Drug Abuse (NIDA) provided funding for collection of additional blood samples and the administration of the drug use disorders assessment. The National Institute of Justice (NIJ) provided support for querying participants about interaction with the Criminal Justice Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 10 publications
2
51
0
2
Order By: Relevance
“…Of the 44,239 fatally injured drivers with drug-tested information in the fi le, about 25% tested positive for drugs (n = 10,997). This fi gure almost doubles the 14% drug prevalence estimated by the 2007 National Roadside Survey (Lacey et al, 2009), suggesting a possible contribution of drugs to the occurrence of fatal crashes. Among the tested drugs, cannabinoids (marijuana, tetrahydrocannabinol [THC], and other cannabinoids) and stimulants (cocaine, amphetamines, benzphetamines, methamphetamines, and other stimulants) were the most prevalent: Each contributed to about 23% of the drug positives.…”
Section: Descriptive Analysismentioning
confidence: 58%
See 1 more Smart Citation
“…Of the 44,239 fatally injured drivers with drug-tested information in the fi le, about 25% tested positive for drugs (n = 10,997). This fi gure almost doubles the 14% drug prevalence estimated by the 2007 National Roadside Survey (Lacey et al, 2009), suggesting a possible contribution of drugs to the occurrence of fatal crashes. Among the tested drugs, cannabinoids (marijuana, tetrahydrocannabinol [THC], and other cannabinoids) and stimulants (cocaine, amphetamines, benzphetamines, methamphetamines, and other stimulants) were the most prevalent: Each contributed to about 23% of the drug positives.…”
Section: Descriptive Analysismentioning
confidence: 58%
“…In the United States, the 2007 National Roadside Survey found that the percentage of drivers who were using drugs (14%) was greater than the percentage who were using alcohol (12%; Lacey et al, 2009). This somewhat startling result led the White House Offi ce of National Drug Control Policy (2010) to call for states to pass drug per se laws in 2010.…”
Section: T He Role Of Drugged Driving In Fatal Crashesmentioning
confidence: 99%
“…Estudos realizados em outros países, com metodologia similar, apresentam taxas de 5% a 14% nas noites dos ns de semana 14,15 . A análise das características dos condutores em todas as regiões do estado não apresentou diferença estatística, apontando para uma homogeneidade da população pesquisada.…”
Section: Discussionunclassified
“…Isso ocorre porque o motorista, apesar de ter ingerido pequena quantidade de álcool e estar aparentemente sóbrio e consciente do risco de beber e dirigir, pode estar intoxicado, adotando o falso senso subjetivo do beber seguro, oferecendo risco para si e para outras pessoas. Mesmo policiais bem treinados frequentemente não são capazes de identi car motoristas sob efeito de álcool 15 . Pesquisa realizada nos Estados Unidos mostrou que mais da metade de motoristas com níveis de alcoolemia acima de 0,5 g/l e 90% com níveis de 0,8 g/l não foram identi cados por policiais militares em postos de checagem de sobriedade 20,22,23 .…”
Section: Discussionunclassified
“…The National Roadside Survey conducted for the National Highway Traffi c Safety Administration in 2007 found that, among drivers ages 16-20 tested at night, 16.1% tested positive for drugs other than alcohol (based on oral fl uids) and 7.2% tested positive for alcohol (based on breath alcohol measurements) (Lacey et al, 2009a(Lacey et al, , 2009b. Given that alcohol-impaired driving fatalities accounted for 31% of the total motor vehicle traffi c fatalities in the United States in 2011 (National Highway Traffi c Safety Administration, 2012), identifying predictors of teenage drinking and driving and RWI is critical to preventing teenage injuries and fatalities.…”
Section: Alcohol-/other Drug-related Crash Riskmentioning
confidence: 99%